Clear, conspicuous, and improving: US corporate websites for critical financial literacy in retirement. Issue 5 (3rd July 2017) - Lee, Taejun (David)
Abstract : Purpose: The economic downturn and financial meltdown in the changing retirement savings and pension landscape in the US placed individual investors and financial companies at risk. Recognizing the need for more financial literacy among investors, the US financial services companies for retirement plans and investment options (i.e. the retirement financial services providers (RFSPs)) have stepped up consumer marketing, particularly through creation of corporate websites. Seeing their potential for increasing literacy and aiding consumer financial decisions, a majority of RFSPs are promoting websites and a large number of consumers use them. With this backdrop, the purpose of this paper is to examine the use of these websites and their conformity to existing regulations regarding design and structure. Design/methodology/approach: The present study used a quantitative content analysis to examine the types of disclosure information presented on the corporate websites of RFSPs during 2013-2015. It also examined the adherence to the Federal Trade Commission's (FTC) clear and conspicuous standards (CCS) disclosure guidelines over the three-year period. Finally, this study examined the levels of financial literacy activities employed on 164 RFSPs' websites over the three-year period. Findings: This study shows that RFSPs are increasingly providing disclosure information for target consumers via their websites. Although problems still exist with the presentation of that material in terms of the FTC's suggestions for prominence, there have been some improvements in compliance with proximity of disclosures. In addition, just under one-fourth of the RFSPs were providing tactics and features on their websites to potentially aid in the creation and maintenance of critical financial literacy and acumen. Practical implications: The key point emerging from this analysis is that financial services providers, regulators, advocacy groups, and policymakers should continue to address varying levels of financial literacy activities to promote the deliberation and discussion of the retirement issues and topics across media while facilitating the provision and dissemination of financial information and data in a clear and conspicuous manner. Originality/value: This is the first study to explore the content of RFSPs' websites with regard to disclosure information, adherence to FTC CCS disclosure guidelines, and the use of techniques related to various levels of financial literacy from 2013-2015.